2011
DOI: 10.1097/tp.0b013e318200ba0e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Administration of Recombinant Human Protein C in Xenografted Primates

Abstract: In this pig to primate model, rhaPC confers a short advantage in the prevention of early perioperative xenograft damage but does not represent an effective strategy for preventing AHXR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Some groups routinely administer continuous heparin to baboon recipients of pig renal (42) and cardiac (140, 141) xenografts, although it is difficult to assess the efficacy of this treatment. Administration of recombinant human antithrombin was clearly protective in the first week after pig-to-baboon renal xenotransplantation (98), but had no apparent long-term benefit in the pig-to-macaque renal model (142), even when combined with human activated protein C (143). Other reagents have also produced mixed results, and it would be reasonable to conclude that both genetic modification and pharmacotherapy will be necessary to fully control inflammation and coagulation in renal xenotransplantation (144).…”
Section: Preventing Kidney Xenograft Rejectionmentioning
confidence: 99%
“…Some groups routinely administer continuous heparin to baboon recipients of pig renal (42) and cardiac (140, 141) xenografts, although it is difficult to assess the efficacy of this treatment. Administration of recombinant human antithrombin was clearly protective in the first week after pig-to-baboon renal xenotransplantation (98), but had no apparent long-term benefit in the pig-to-macaque renal model (142), even when combined with human activated protein C (143). Other reagents have also produced mixed results, and it would be reasonable to conclude that both genetic modification and pharmacotherapy will be necessary to fully control inflammation and coagulation in renal xenotransplantation (144).…”
Section: Preventing Kidney Xenograft Rejectionmentioning
confidence: 99%
“…These disparities may also contribute to systemic derangement of coagulation parameters sometimes reported after xenotransplantation (63). Systemic therapies using clinical antiplatelet and antithrombotic drugs or using activated protein C fail to prevent MT, fibrin deposition, or prolong xenograft survival (6468). This result may be due to the level of redundancy in haemostatic regulation, the intensity of non-Gal antibody-mediated rejection, or a failure to durably control haemostasis at the surface of the vascular EC.…”
Section: Coagulation and Xenograft Rejectionmentioning
confidence: 99%
“…However, all xenografts were eventually lost to humoral rejection at 5 weeks and exhibited significant fibrin staining at explant. This lack of effect on the long-term outcome may have been because of failure to achieve a sufficient local concentration of rhAPC to counter developing rejection (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human APC (rhAPC) is used clinically for the treatment of severe sepsis, although its use is associated with a modestly increased risk of spontaneous hemorrhage (36). Simioni et al reported that continuous infusion of rhAPC prevented fibrin deposition in pig-to-monkey renal xenografts in the first 2 weeks after transplantation, without causing serious bleeding problems (37). However, all xenografts were eventually lost to humoral rejection at 5 weeks and exhibited significant fibrin staining at explant.…”
Section: Discussionmentioning
confidence: 99%